Knowledge and awareness of Middle East respiratory syndrome coronavirus among Saudi and Non-Saudi Arabian pilgrims - Althobaity, Hosam M.; Alharthi, Raed A. S.; Altowairqi, Mohammed H.; Alsufyani, Ziyad A.; Aloufi, Nahar S.; Altowairqi, Abdulrahman E.; Alqahtani, Abdulrahman S.; Alzahrani, Ali K.; Abdel-Moneim, Ahmed S. (International Journal of Health Sciences, 2017)
Objective: The current study was intended to evaluate the knowledge and awareness toward Middle East respiratory syndrome coronavirus (MERS-CoV) of pilgrims from Saudi Arabia and from different Arabian countries. Methods: A prospective study was conducted among pilgrims from Saudi Arabia and those from other Arab nations. A total number of 2120 participants including 736 Saudi pilgrims (436 males and 300 females) and 1384 non-Saudi Arabian pilgrims (1384; 909 males and 475 females) were included in the study. The responses of the participants were descriptively analyzed. Pearson correlation coefficient was used to screen the possible correlations among different variables. The differences in the responses between the two groups were evaluated using Mann–Whitney analysis. Results: The responses of the Saudi pilgrims showed statistically significant results in comparison to non-Saudi pilgrims in answering all questions except those related to the presence of efficient vaccination or treatment and the source of information. It was clear that the Saudi pilgrims were more oriented about different aspects of MERSCoV including the nature of the causative agent, the signs, the severity of the disease, the animals that can transmit the infection to humans, the risk groups, and when one need to be screened for infection. In both Saudi and non-Saudi pilgrims, the official websites of health organizations constitute the main source of their information. Conclusion: It was concluded that Saudi pilgrims possess good knowledge about the MERS-CoV although more orientation is still required.